A rhetorical analysis of political discourse barack obama political speech “a more perfect union - Pusparini , Ni Wayan; Suastini, Ni Wayan; Jayantini, I G A Sri Rwa (Journal of Language and Applied Linguistics, 2020)
This study aims to identify the rhetorical proof used in Barack Obama political speech. This paper related to public speaking skills as a public figure especially as a politician. Basically the relationship between Public speaking and rhetorical defined as persuasive speaking in public oratory and rhetorical as an art of language kindly a figure of speech in order to persuade and create memorable speech. Rhetoric words usually use to avoid impolite statements and ruin the image of the speaker itself. The data were analyzed with descriptive qualitative method. This study used theory of rhetorical proofs by Aristotle in Griffin (2012) which consisted of three appeals such as logos (logical proof), ethos(ethical proof), and pathos (emotional proof). The result of this study showed that the most dominant rhetorical proof is pathos (emotional proof) especially in fear type. The highlight Barack Obama’s political speech concerned racial tension happened which is the most serious problem in America. Fear types as dominant proof surfaces as the sadness of troubles that faced in America society and the chance of Barack Obama to give campaign to choose him as president.